Classification Of Flat Spectrum Radio Quasars By Optical Activity Types - Mickaelian, A. M.; Abrahamyan, H. V.; Paronyan, G. M.; Mikayelyan, G. A.; Sukiasyan, A. G.; Mkrtchyan, V. K.
We have carried out a spectral classification by the activity types for a subsample of blazars from the BZCAT v.5 Catalogue, namely the Flat Spectrum Radio Quasars (FSRQ) candidates, designated in the catalogue as BZQ subtype objects. The classification is based on the Sloan Digital Sky Survey (SDSS) homogeneous medium-resolution optical spectroscopy and along with the standard BPT-type diagnostic diagrams, we have applied our newly introduced fine classification scheme with subtypes of quasars and considering many more features. Out of 1909 BZQ objects, 618 having SDSS spectra were classified, resulting in 445 broad-line QSOs, 19 narrow-line QSOs, 138 broad-line Seyferts, 8 narrow-line Seyferts, and 2 Emission-line galaxies without a proper classification. We have calculated the absolute magnitudes and luminosities for all objects to distinguish QSOs from Seyferts, as defined by the Catalogue of QSOs and Active Galaxies, -22m.25 separation limit. This way 148 objects changed their BZCAT subtypes between BZQ to BZG, and also 6 BZQ objects to BZU. Проведена спектральная классификация кандидатов в радиоквазары с плоским спектром (FSRQ) из каталога BZCAT v.5, обозначенные в каталоге как объекты подтипа BZQ. Классификация основана на оптической спектроскопии среднего разрешения Слоановского цифрового обзора неба (SDSS), и наряду со стандартными диагностическими диаграммами BPT- типа применена недавно введенная авторами схема тонкой классификации с подтипами квазаров и учетом многих других особенностей. Из 1909 BZQ объектов классифицированы 618, которые имеют спектры SDSS, в результате чего имеем: 445 квазаров с широкими линиями, 19 квазаров с узкими линиями, 138 Сейфертов с широкими линиями, 8 Сейфертов с узкими линиями и 2 эмиссионные галактики. Рассчитаны абсолютные звездные величины и светимости для всех объектов, чтобы отличить QSO от сейфертовских галатик, как это определено каталогом квазаров и активных галактик c пределом разделения -22m.25. В результате, 148 объектов изменили свой BZCAT подтип между BZQ и BZG, а 6 объектов с BZQ на BZU.
Keywords: Astrophysics